Thin layer solar drying and mathematical modeling of mulberry - Akbulut, Abdullah; Durmus, Aydin (Wiley, 2009)
In this study, drying parameters of mulberry grown in Elazig were investigated as experimental and theoretical using solar dryer system. The drying experiments were conducted at seven different drying mass flow rates varied between 0.0015 and 0.036 kg s(-1). As results of the drying experiments were conducted at different drying mass flow rates, it was shown that the drying time was decreased with the drying mass flow rate. This paper also presents a new mathematical modeling of thin layer solar drying of mulberry samples. In order to estimate the suitable form of solar drying curves, 10 different mathematical models to be in the literature and new model were applied to the experimental data and compared according to their correlation coefficients (R) and chi-squared (chi(2)), which were predicted by non-linear regression analysis using the Statistica Computer Program. It was concluded that the Midilli model and the newly developed model represent drying characteristics better than the other models. The effective moisture diffusivity values were in the range 3.47 x 10-(12)-1.46 x 10(-9) m(2) s(-1). Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: solar energy; solar air heater; drying; mathematical modeling; mulberry; forced drying; diffusion coefficient